Replication of nuclear polyhedrosis virus in a continuous cell culture of Spodoptera frugiperda: microscopy study of the sequence of events of the virus infection - Knudson, D L; Harrap, K A (Journal of virology, 1976)
A microscopy study of the sequence of morphogenic events of Spodoptera frugiperda nuclear polyhedrosis virus infection of S. frugiperda cells is presented which orders the sequence of replication and establishes the time scale within which the events occur. The virus entered the cell by 1 h postinfection and was uncoated. The eclipse period was 9 h and the latent period was 12 h. Polyhedron formation was detected by 18 h postinfection and continued until the deposition of the polyhedron membrane was completed by 48 h postinfection. Aberrant morphogenic characteristics of virus repeatedly passaged in the cell culture were also recorded. Adsorption, envelope morphogenesis, and release mechanisms are discussed in light of other data on in vivo and in vitro baculovirus infections.